Corporate Social Responsibility and competitiveness of a Peruvian agro-exporting company in an emerging economy - Farro Ramirez, Claudia Madelyn; Cosio Borda, Ricardo Fernando; Ramírez-Briones, Lorena; Cajavilca-Gonzáles, Berenice; Noriega-Monar, Gloria; De la Cruz Montoya, David; Pajuelo Rodríguez, James Arístides (LACCEI, 2025)
The general objective of the research was to establish the relationship between corporate social responsibility (CSR) and the competitiveness of an agro-exporting company in Piura in the year 2024. A quantitative approach was used, applied type, correlational level, non-experimental and cross-sectional design; a survey was conducted using a questionnaire as an instrument to the final population of 52 workers of the company. The results indicated a moderate and statistically significant positive correlation between the CSR and competitiveness variables, with a Spearman’s Rho coefficient of 0.640, with a bilateral significance of less than 0.001. Thus, it was concluded that, as CSR practices increased in the economic, social and environmental areas, the company’s competitiveness also increased, although not proportionally.